STUDI KINETIKA ADSORPSI ION Fe (III) MENGGUNAKAN LIMBAH AMPAS SAGU - Batseba Taihuttu; V Kayadoe; A Mariwy (Molluca Journal of Chemistry Education (MJoCE), 2019)
Adsorption study of the adsorption of heavy metal ions from Fe (III) using sago dregs waste was carried out. adsorption was carried out in batches, with the mass of adsorbent is 1 g and the concentration of Fe (III) ion is 10 ppm. in this study variations in contact time were 60, 90, 120, 150 and 180 minutes to determine the kinetic suitable for the adsorption process of ion Fe (III) and the capacity and efficiency of sago dregs adsorption. The results showed that the adsorption of ion fe (III) using sago dregs followed pseudo second-order kinetics with R2 values that were closer to 1 that is 0,9651. adsorption of ion Fe (III) at optimum contact time of 90 minutes with adsorbent mass of 1 g obtained by adsorption capacity 0,3211 mg/g and the adsorption efficiency is 64,2%.